PROSES KERJA TIM DIVISI HEALTH CARE DALAM PELAYANAN KESEHATAN DI TEVIS FOUNDATION - Risya Ananda Putri (Social Welfare Study Program, 2022)
Abstract. Teamship or teamwork is one part of the administration, which together with leadership can bring the organization to life and bring the results desired by the organization. If understood and put into practice, leadership and teamwork can make significant changes in the delivery of social services. The provision of services in the Health Care division is complex and has more and more challenges, especially during the Covid-19 pandemic, therefore efforts are needed to improve teamwork so that the organization becomes more effective and efficient. The efforts of the team and its leaders in social work practices have an impact on the performance of the social services provided and the performance of the institution, so an analysis of the teamwork process is needed to determine the extent to which health service delivery at the Tevis Foundation can be effective and efficient in providing its services to the community. The purpose of this study was to explore the work process of the Tevis Foundation team that puts forward management roles, where the management roles that are implemented emphasize the teamship element proposed by Skidmore (1995), including communication, compromise, cooperation, coordination, and consumption. This type of research uses a qualitative research approach with research instruments used in data collection, namely interview guidelines, observation guidelines, and field studies. The technique used is in-depth interviews, non-participant observation. The informant of this research is the Health Care division of the Tevis Foundation which is in direct contact with the beneficiaries. The findings of this study are that the role of teamwork process plays an important role in an organization to provide health services to the community starting from communication to program consumption to minimize errors that exist in an organization. The team's ability to adapt to adversity, and to be able to place themselves with the challenges that exist is one of the keys to the success of humanitarian service organizations in the health sector. Keywords: Teamwork process, Health Services, Management Roles, Covid-19 Abstrak. Teamship atau kerja tim merupakan salah satu bagian dari administrasi, yang bersama dengan kepemimpinan dapat menghidupkan organisasi dan membawa hasil yang diinginkan oleh organisasi. Kepemimpinan dan kerjasama tim jika dipahami dan dipraktikkan maka dapat membuat perubahan yang signifikan dalam penyampaian layanan sosial. Pemberian layanan di divisi Health Care yang kompleks dan semakin banyak tantangan terutama di masa pandemi Covid-19, oleh karena itu diperlukan upaya untuk meningkatkan teamwork agar organisasi menjadi lebih efektif dan efisien. Upaya tim dan pimpinannya dalam praktik pekerjaan sosial memberikan dampak terhadap kinerja dari layanan sosial yang diberikan maupun kinerja dari lembaga tersebut, sehingga analisa terhadap proses kerja tim diperlukan untuk mengetahui sejauh mana pemberian layanan kesehatan di Tevis Foundation dapat efektif dan efisien dalam memberikan layanannya kepada masyarakat. Tujuan penelitian ini adalah untuk mengeksplorasi proses kerja tim Tevis Foundation yang mengedepankan management roles, dimana management roles yang dilaksanakan menekankan kepada elemen teamship yang dikemukakan Skidmore (1995), meliputi komunikasi, kompromi, kooperasi, koordinasi, dan konsumasi. Jenis penelitian menggunakan pendekatan penelitian kualitatif dengan instrumen penelitian yang digunakan dalam pengumpulan data yaitu pedoman wawancara, pedoman observasi, dan studi lapangan. Teknik yang digunakan adalah wawancara mendalam, observasi non-partisipan. Informan dari penelitian ini adalah divisi Health Care dari Tevis Foundation yang berhubungan langsung dengan penerima manfaat. Temuan dari penelitian ini yaitu peran dari proses kerja tim memegang peranan penting dalam sebuah organisasi untuk memberikan layanan kesehatan kepada masyarakat dimulai dari komunikasi hingga konsumasi program agar dapat meminimalisir kesalahan yang ada dalam sebuah organisasi. Kemampuan tim dalam menyesuaikan diri dengan kesulitan, dan mampu menempatkan diri dengan tantangan yang ada adalah salah satu kunci keberhasilan organisasi pelayanan kemanusiaan dalam bidang kesehatanKata kunci: Proses kerja tim, Layanan Kesehatan, Management Roles, Covid-19